The New Keynesian Phillips Curve and staggered price and wage determination in a model with firm-specific labor - Mikael Carlsson; Andreas Westermark (Uppsala University, Department of Economics, 2009)
We develop a DSGE model with firm-specific labor where firm-level wage bargaining and price setting are subject to Calvo-type staggering. This is in general an intractable problem due to complicated intertemporal dependencies between price and wage decisions. However, the problem is significantly simplified if we, in line with empirical evidence, assume that prices can be changed whenever wages are. We show that the price- and wage-setting relationships are substantially altered by the introduction of firm-specific labor. Specifically, the inflation response is substantially dampened, whereas the wage inflation response is increased as compared to models with freely mobile labor. These distinctive features of the model with firm-specific labor is supported by empirical evidence from a structural VAR.
Keywords: C72; C78; D62; 330; Monetary Policy; Inflation Persistence; Labor Market; Bargaining